A Pragmatic Study of Selected Pairs of Iraqi-Kurdish Proverbs - Mugair , Sarab Kadir (International Journal of Psychosocial Rehabilitation, 2025)
The focus of this study is to analyze Kurdish proverbs from a pragmatic perspective. To achieve its aims, the study tries to identify the forms and functions of these Kurdish proverbs as they are used in everyday life. The study starts with a brief introduction to proverbs, its relatively specific to the general formation of proverbs and their pragmatic functions for giving positively satisfactory communication sequences. Followed by a brief explanation and two important pragmatic principles observed in actual application in concrete, the context in which certain practical functions are effectively performed. The last part of study focuses primarily on the actual use of (10) Kurdish proverbs in everyday life, with some explaining how to use Kurdish proverbs based on these practical principles to perform a particular function. Showing (10) examples and providing some application methods to help the reader understand and practice basic linguistic theory.